A Papillary Thyroid Microcarcinoma Revealed by a Single Bone Lesion with No Poor Prognostic Factors - Yann Godbert; Benedicte Henriques-Figueiredo; Anne-Laure Cazeau; Xavier Carrat; Marc Stegen; Isabelle Soubeyran; Francoise Bonichon (Case Reports in Endocrinology)
Objectives. Thyroid carcinomas incidence, in particular papillary variants, is increasing. These cancers are generally considered to have excellent prognosis, and papillary microcarcinomas are usually noninvasive. Many prognostic histopathology factors have been described to guide therapeutic decisions. Most patients are treated with total thyroidectomy without radioiodine treatment or partial surgery. Case Summary. A 65-year-old man with no significant medical history presented with pain in the left chest wall that had been present for several months. A computed tomography (CT) found a large tissue mass of 4 cm responsible for lysis of the middle arch of the 4th rib on the left. It was a single lesion, highly hypermetabolic on the 18-FDG PET/CT. The histology analysis of the biopsy and surgical specimen favored an adenocarcinoma with immunostaining positive for TTF1 and thyroglobulin (Tg). The total thyroidectomy carried out subsequently revealed a 4 mm papillary microcarcinoma with vesicular architecture of the right lobe, well delimited and distant from the capsule without vascular embolisms. After two radioiodine treatments, the patient is in complete clinical, biological, and radiological remission. Conclusion. This extremely rare case of a singular bone metastasis revealing a papillary thyroid microcarcinoma illustrates the necessity of further research to better characterize the forms of papillary thyroid microcarcinomas with potentially poor prognosis.